Hydrous ruthenium oxide-tantalum pentoxide thin film electrodes prepared by thermal decomposition for electrochemical capacitors. Issue 10 (July 2020) - Xie, Jian-De; Hsu, Kai-Hsiang; Patra, Jagabandhu; Su, Ching-Yuan; Lee, Sheng-Wei; Ashraf Gandomi, Yasser; Ger, Ming-Der; Pu, Nen-Wen; Chang, Jeng-Kuei
Abstract: In this work, we have fabricated high-performance thin-film electrodes for electrochemical capacitors (ECs) via thermal decomposition syntheses of RuO2 –Ta2 O5 coating layers on Ti substrates. The influences of decomposition temperature as well as the Ru/Ta molar ratio on material and electrochemical properties of the EC electrodes are systematically investigated. The thermal decomposition of 300 °C preserves a large fraction of hydrous RuO2 · x H2 O within the hybrid oxide and consequently improves the electrode capacitance. The amorphous Ta2 O5 incorporation can manipulate the RuO2 crystallinity and thus its specific capacitance. An optimal Ru/Ta molar ratio of 7:3 is determined for the RuO2 –Ta2 O5 electrode, which can deliver an energy density of 4.8 Wh kg −1 at a power density of 8720 W kg −1 (or 8.3 Wh L −1 at 15, 000 W L −1 ). In addition, an excellent durability of 97.6% capacitance retention after 3000 charge-discharge cycles is found for this electrode. The proposed RuO2 –Ta2 O5 thin-film electrode has paved the way for next-generation ECs with superior capacitances, energy/power densities, and cyclability.